Dinamika Kepemimpinan Pondok Pesantren - ARIFIN, SAMSUL (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
The writer conducted a qualitative research approach of social phenomenology;the data in this study were collected by using observation, in-depth interviews, anddocumentations. In order to articulate the leadership of the Islamic boarding school,the data has been analyzed by using qualitative methods with the mindset ofdeductive-inductive. The process of data analysis carried out in phases: datareduction, data presentation, and conclusion.The dynamics of leadership in Islamic boarding school. The figure of Kiai isthe central figure and more of it is a determinant factor to the success of studentsin the search for knowledge, leadership models used a model of democraticleadership. In that sense, all the information from the outside before being madepolicies (rules) boarding schools, first in the filter by a caregiver. Developmentprograms are prioritized in formal and non-formal. The inhibitors of Islamicboarding school leadership, namely: Human Resource students, education funds,and the interest of society to change the tendency towards salafiyah and modernvalues. Supporting; Their means of education oriented to the development ofstudents, and institutions that help students accommodate their talents andinterests to develop.AbstrakPondok pesantren merupakan lembaga pendidikan Islam yangmenempatkan sosok kiai sebagai tokoh sentral dan masjid atau surausebagai pusat lembaganya. Lembaga ini merupakan institusi pendidikanIslam tertua di Indonesia dan sekaligus merupakan bagian dari warisanbudaya bangsa (indigenous culture). Maka, bukanlah kebetulan jikapesantren masih dapat bertahan hingga saat ini.Dinamika kepemimpinan di pesantren. Sosok kiai merupakan figursentral dan lebih dari itu merupakan faktor determinan terhadapsuksesnya santri dalam mencari pengetahuan, model kepemimpinanmenggunakan model kepemimpinan demokrasi. Dalam artian, Semuainformasi dari luar sebelum dijadikan kebijakan (aturan) pesantren,terlebih dahulu di filter oleh pengasuh. Pengembangan programdiprioritaskan pada pendidikan formal dan non-formal. Penghambat darikepemimpinan pesantren ini, yaitu: Sumber daya santri, Dana pendidikan,dan Minat masyarakat yang mengalami perubahan kecenderunganterhadap nilai salafiyah dan modern. Penunjangnya; Adanya saranapendidikan yang berorientasi pada pengembangan santri, dan lembagayang membantu santri mengakomodir bakat dan minatnya untukberkembang.